PEMBUATAN COOKIES SUBSTITUSI TEPUNG TALAS (Colocasia esculenta (L) Schot) DAN TEPUNG DAUN KELOR (Moringa oleifera Lamk) - Dila Yunita Ardianti; Rista Anggriani; Sukardi Sukardi (Universitas Muhammadiyah Malang, 2019)
Cookies are products that have a sweet taste with ingredients derived from wheat flour. Wheat flour can be replaced with local raw materials, such as taro flour. Moreover, cookies need to be added to functional compounds, namely Moringa leaf flour which has antioxidant properties and give a green color to the product produced. The purpose of this study was to determine the physical-chemical and organoleptic cookies substituted with taro flour and fortified with Moringa leaf flour and to determine the effect of using taro flour and Moringa leaf flour on antioxidant activity in cookies. This study used a Completely Randomized Design (CRD) which is arranged in a simple manner and with data retrieval, in which each study carried out 4 replications. The factor was the concentration of taro flour and moringa leaf flour. The parameters analyzed were water content, ash, protein, fat, carbohydrate, fiber, the activity of antioxidants, and color. While the organoleptic tests were color, taste, and texture. Cookies for substitution of taro flour and fortification of moringa leaf flour have a very significant effect on K1 (Wheat flour 40 g + Taro flour 50 g + Moringa leaf flour 10 g) on parameters 1,92% of water, 2,11% of ash, 23,34% of fat, 7,52% of the protein in color parameters produces greenish color (a-) 4.65 and yellowish color (b +) 15,83, and organoleptic test appearance 2,60, in treatment K5 (Wheat Flour 40 g + Taro flour 58 g + Moringa leaf flour 2 g) had a very significant effect on fiber content parameters 0,18%, carbohydrate content 71,59%, texture 36,43 N / m2 and in the organoleptic test taste 3.60, treatment K4 ( K4: 40 g of Wheat flour, 56 g of Taro flour, 4 g of Moringa leaf flour) has the highest brightness test value (L) of 46,00 and in the highest value organoleptic parameters of treatment K3 (40 g of Wheat Flour, 54 g of Taro Flour, 6 g of Moringa leaf flour) of 2,75.